Selling war in a media age : the presidency and public opinion in the American century - Osgood, Kenneth Alan, 1971-; Frank, Andrew, 1970- (Alan B. Larkin series on the American presidency., 2010)
George W. Bush's 'Mission Accomplished' banner in 2003 and the misleading linkages of Saddam Hussein to the 9/11 terrorist attacks awoke many Americans to the techniques used by the White House to put the country on a war footing. Yet Bush was simply following in the footsteps of his predecessors, as the essays in this standout volume reveal in illuminating detail.